Ethnic patterns of hypospadias in New Zealand do not resemble those observed for cryptorchidism and testicular cancer: evidence of differential aetiology?. (13th November 2015) - Gurney, J. K.; Stanley, J.; Shaw, C.; Sarfati, D.
Summary: It has been proposed that hypospadias, cryptorchidism, poor semen quality and testicular cancer might share common prenatal causes. We have previously demonstrated similar ethnic patterns for the incidence of testicular cancer and cryptorchidism – a known risk factor for testicular cancer. If the underlying exposure(s) that cause hypospadias, cryptorchidism and testicular cancer are shared, then we would expect the incidence relationship between ethnic groups to follow the same pattern across all three conditions. We followed a birth cohort of 318 345 eligible male neonates born in New Zealand between 2000–2010, and linked routinely collected maternity records with inpatient hospitalization and mortality records through to 2011. We searched hospitalization records for diagnoses of hypospadias, and used mortality records for censoring. We used Poisson regression methods to compare the relative risk of hypospadias between ethnic groups, adjusting for perinatal risk factors and total person time. We observed that European/Other children had the highest risk of hypospadias, with Māori, Pacific and Asian boys having around 40% lower risk of disease compared with this group (adjusted relative risk [RR]: Māori 0.62, 95% CI 0.55–0.70; Pacific 0.62, 95% CI 0.53–0.72; Asian 0.57, 95% CI 0.47–0.69). This contrasts substantially with our previous observations for cryptorchidism and testicular cancer, where Māori males have the greatest risk. Our observations suggest that – at least in New Zealand – the exposures that drive the development of hypospadias may differ to those that that drive the development of cryptorchidism and/or testicular cancer.